Mathematical modeling for computational simulation of the temperature distribution during the synthesis of polycrystalline diamond - Rangel,João José de Assis (2006)
The properties and structural characteristics of polycrystalline diamonds synthesized at high pressure and high temperature are strongly influenced by the distribution of temperature inside the reaction chamber. This distribution cannot be directly measured during the graphite to diamond transformation. In this work a mathematical model associated with a computational analysis was developed to simulate the chamber, point to point, temperature distribution throughout the synthesis process. The simulation results obtained are in agreement with experimental data found in the literature. Moreover, it was possible to explain the restriction that exists regarding the use of graphites with different densities.